AN INVESTIGATION TO IDENTIFY THE PROBLEMS FACED BY THE STUDENTS IN LEARNING MATHEMATICS AT THE UNDER GRADUATE LEVEL OF KAMRUP (M) DISTRICT OF ASSAM - Gunendra Chandra Das, Mrinal Sarma, ManashPratim Kashyap (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The potential problems and challenges that student of Kamrup (M), Assam faces while learning mathematics have been highlighted in this study. The principle focus here is to understand the factors related to perception of mathematics, teaching methods, teaching elements or techniques and efficiency among the students. The undergraduate students and their abilities or interest in mathematics have been prioritised in this study. This paper also signifies the importance of selecting this topic. The degrading interest and motivation among the undergraduate students of Kamrup (M) region is the principal rationale behind choosing this topic for discussion.